Role of prokineticins and T-reg cells in obesity-associated metabolic oxidative dysregulation in NAFLD - Prakash, Shyam; Priyatma; Aasarey, Ram; Khan, Shahid; Vikram, Naval K.; Shalimar; Medha; Srivastava, Saumya; Pandey, Shivam; Priya, Akanksha; Aggarwal, Sandeep (Scientific reports, 2025)
We investigate the role of prokineticin, T-reg cells, and oxidative metabolism in the progression of obesity-related NASH to HCC. Our findings on a cohort of 250 patients, including Obese NAFLD and Non-Obese NAFLD, reveal significant insights. In Obese NAFLD, PK-1 mRNA expression was reduced by 2.4-fold ( p < 0.01) compared to Non-Obese NAFLD, while PK-2 was upregulated by 1.4-fold ( p < 0.005), and FABP-5 increased by 1.4-fold ( p < 0.005) compared to T2DM. IL-10 mRNA expression was 2.4-fold higher ( p < 0.005) in MetS verses to Non-Obese NAFLD. Nrf-2 expression was elevated by 1.13-fold in Non-Obese NAFLD compared to Obese NAFLD ( p < 0.05). Flow cytometric analysis of T-reg cells was three times lower in Obese NAFLD compared to MetS ( p < 0.005), with a notable reduction in CD8 + cells and an increase in CD4 + cells. Correlation analysis in Obese NAFLD revealed strong positive correlations between IL-10 and T-reg ( r = 1), CD4 + ( r = 0.99), and CD8 + cells ( r = 0.99). PK-1 expression correlated with CD8 + cells ( r = 0.52), while PK-2 negatively correlated with C-type lectin ( r =-0.49). FABP-5 exhibited significant positive correlations with PK-1 ( r = 0.54) and IL-10 ( r = 0.63). We highlight the interplay between prokineticins, immune modulation, and metabolic oxidative factors to offer potential therapeutic targets to prevent progression to HCC, instilling hope for the future of NASH treatment.